2015
DOI: 10.1111/coa.12322
|View full text |Cite
|
Sign up to set email alerts
|

The use of Tisseel fibrin sealant in selective neck dissection – a retrospective study in a tertiary Head and Neck Surgery centre

Abstract: The use of Tisseel in SND resulted in lower drain output and shorter period of drain in situ and hospitalisation. There was no additional morbidity or complication associated with its use, and the initial conclusion is that this technique may have benefits not only to patient recovery but also for healthcare providers as they could potentially reduce the overall costs of surgery by reducing the length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…The results are inconsistent with a previous study conducted in the United Kingdom [11]. A possible explanation for this discrepancy might be that the abovementioned study employed a retrospective design, while our study used a prospective randomized approach.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results are inconsistent with a previous study conducted in the United Kingdom [11]. A possible explanation for this discrepancy might be that the abovementioned study employed a retrospective design, while our study used a prospective randomized approach.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous retrospective study found that the mean drainage amount was 67.1 ml for patients with fibrin glue applied in the wound and 174.4 ml for those without [11]. The null hypothesis was that there would be no clinically meaningful difference in drainage duration between those receiving and those not receiving fibrin glue, and the alternative hypothesis was that the drainage duration of those receiving fibrin glue would be shorter than that of those not receiving fibrin glue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The premise that FS is of greater benefit in patients having lateral neck dissection is supported by two non‐randomised studies that both showed a clear benefit of using tissue adhesives (FS or autologous platelet and plasma adhesives). This is in terms of both total wound drainage and retention time of drains …”
Section: Discussionmentioning
confidence: 99%
“…Our department has used a fibrin sealant spray post‐neck dissection for several years in an attempt to reduce post‐operative seroma formation. Our results have been published demonstrating that the use of Tisseel™ tissue glue reduced both the length of stay and the volume drained when compared to previous surgical groups not receiving tissue sealant . Since that study was published, our department moved to using a newer Baxter™ product, Artiss™.…”
Section: Introductionmentioning
confidence: 99%